Pelatihan Konten Kreator dalam Mendukung Masyarakat Informasi di Era Industri 5.0 di SMK Diponegoro Banyuputih Batang - Setiawan, Hendy; Choirunnisa, Choirunnisa (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this article is to explain the results of community service carried out by the service team at Diponegoro Banyuputih Vocational School, Batang Regency. This service is carried out by training content creators for vocational school students, especially in facing industry 5.0 competition. As we all know, Batang Regency since 2020 has been designated by President Joko Widodo as a strategic area for national industrial development. Therefore, in developing this industrial area, local communities are required to prepare and adapt in the face of rapid industrial competition. Moreover, currently Batang is an area that is officially designated as the Batang Integrated Industrial Area. This service uses a participatory training approach at Vocational School Diponegoro Banyuputih. The results show that in implementing the service, Diponegoro Vocational School students were very enthusiastic and enthusiastic about participating in content creator training. Lots of questions and answers were created so that students had more and more insight into the world of industry.